2006
DOI: 10.1089/pho.2006.24.377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phototherapy on Delayed Onset Muscle Soreness

Abstract: The results of this study provide scientific evidence that phototherapy as used in this study provides a beneficial effect to patients who may experience DOMS after a novel exercise session.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 16 publications
2
42
1
1
Order By: Relevance
“…It is well known that muscle damage often occurs after high intensity exercise, and is accompanied by an inflammatory response [19]. Previous studies have shown that inflammatory responses occur after high intensity exercise [19][20][21][22], and one study found a reduction in delayed onset muscle soreness after eccentric exercise [23]. It is surprising that CRP levels actually are significantly lower than the pre-exercise level for the LEDT group.…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that muscle damage often occurs after high intensity exercise, and is accompanied by an inflammatory response [19]. Previous studies have shown that inflammatory responses occur after high intensity exercise [19][20][21][22], and one study found a reduction in delayed onset muscle soreness after eccentric exercise [23]. It is surprising that CRP levels actually are significantly lower than the pre-exercise level for the LEDT group.…”
Section: Discussionmentioning
confidence: 98%
“…Possible explanations are that although the grip motion may involve a minimal eccentric contraction while releasing the grip, the movement was primarily isometric because the subjects were told to hold the contraction for three seconds. Although eccentric exercise is known as the primary facilitator of DOMS, unaccustomed physical exercise has also been cited as a factor [3]. Grip is a common activity that is utilized is daily.…”
Section: Discussionmentioning
confidence: 99%
“…DOMS was assessed by using the Visual Analogue Scale (VAS). This was previously utilized in another DOMS study by the author [3]. Following each treatment condition, each subject was asked to rate their highest level of pain over the previous 24 hour and 48 hour period by marking a graphic pain scale on a 100 mm line marked no pain on one end and maximal pain on the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise-induced DOMS produces signs and symptoms similar to acute injury, with pain and impairment peaking at 24 to 48 hours postinjury and full resolution within 5 to 7 days. 14,15 The exercise-induced DOMS model mimics the cellular and functional processes observed in acute musculoskeletal injury. [15][16][17][18][19] Such processes include loss of ROM and strength, resting pain (as assessed using the Brief Pain Inventory [BPI]), disability with activities of daily living, and localized swelling followed by signs of healing within 72 hours of injury.…”
mentioning
confidence: 99%